Developing a research and practice tool to measure walkability: a demonstration project. (8th December 2014) - Giles‐Corti, Billie; Macaulay, Gus; Middleton, Nick; Boruff, Bryan; Bull, Fiona; Butterworth, Iain; Badland, Hannah; Mavoa, Suzanne; Roberts, Rebecca; Christian, Hayley
Abstract : Issue addressed: Growing evidence shows that higher‐density, mixed‐use, pedestrian‐friendly neighbourhoods encourage active transport, including transport‐related walking. Despite widespread recognition of the benefits of creating more walkable neighbourhoods, there remains a gap between the rhetoric of the need for walkability and the creation of walkable neighbourhoods. Moreover, there is little objective data to benchmark the walkability of neighbourhoods within and between Australian cities in order to monitor planning and design intervention progress and to assess built environment and urban policy interventions required to achieve increased walkability. This paper describes a demonstration project that aimed to develop, trial and validate a 'Walkability Index Tool' that could be used by policy makers and practitioners to assess the walkability of local areas; or by researchers to access geospatial data assessing walkability. The overall aim of the project was to develop an automated geospatial tool capable of creating walkability indices for neighbourhoods at user‐specified scales. Methods: The tool is based on open‐source software architecture, within the Australian Urban Research Infrastructure Network (AURIN) framework, and incorporates key sub‐component spatial measures of walkability (street connectivity, density and land use mix). Results: Using state‐based data, we demonstrated it was possible to create an automated walkability index. However, due to the lack of availability of consistent of national data measuring land use mix, at this stage it has not been possible to create a national walkability measure. The next stage of the project is to increase useability of the tool within the AURIN portal and to explore options for alternative spatial data sources that will enable the development of a valid national walkability index. Conclusion: AURIN's open‐source Walkability Index Tool is a first step in demonstrating the potential benefit of a tool that could measure walkability across Australia. It also demonstrates the value of making accurate spatial data available for research purposes. So what?: There remains a gap between urban policy and practice, in terms of creating walkable neighbourhoods. When fully implemented, AURIN's walkability tool could be used to benchmark Australian cities against which planning and urban design decisions could be assessed to monitor progress towards achieving policy goals. Making cleaned data readily available for research purposes through a common portal could also save time and financial resources. Abstract : Growing evidence shows that higher‐density, mixed‐use, pedestrian‐friendly neighbourhoods encourage active transport, including transport‐related walking. However, there is little objective data to benchmark the walkability of neighbourhoods within and between Australian cities in order to monitor planning and design intervention progress, and assess built environment and urban policy interventions required to achieve increased walkability. This demonstration project developed, trialled and validated a 'Walkability Index Tool' that could be used by policy makers and practitioners to assess the walkability of local areas; or by researchers to access geospatial data assessing walkability.